Mental health literacy of Australian youth sport coaches - Moore, M. A.; Reynolds, J. F.; Durand, J.; Trainor, K.; Caravaglia, G. (Frontiers in Sports and Active Living, 2022)
Sport is an integral part of Australian culture and comprises a significant portion of time for Australian youth. Within Australia, 73.4% of children reported participating in sport once a week in the latest AusPlay survey (Australian Sports Commission, 2016). Sport historically yields positive health benefits for children and adults. The positive benefits of sport can permeate Australian society. For Australian youth, sport improves mood, enhances neurological functioning, combats chronic disease, and improves biopsychosocial development (Australian Sports Commission, 2016). However, recent national inquiries challenged this exclusively positive conception of sport in Australia, finding sports are institutions that can conceal instances of mental health challenges (Australian Human Rights Commission, 2020). Researchers found ranges of psychiatric disorders in youth athletes ranges from 4 to 68% (Elbe and Nylandsted Jensen, 2016).